КОСМЕТОЛОГИЧЕСКИЕ ПРОБЛЕМЫ ДСТ: КЛИНИКО-ЭКСПЕРИМЕНТАЛЬНОЕ ОБОСНОВАНИЕ ПЕРСПЕКТИВ МЕЗОТЕРАПИИ - Н. Ю. Кононова; Т. Ю. Чернышова; Е. Г. Бутолин; О. В. Данилова (SINAPS LLC, 2015)
This paper discusses dynamics of collagen metabolism, woman' GAGs participating in comprehensive treatment of the aging process of skin. The results were confirmed by an experiment on white rats.